Management control systems package, corporate governance, and SME’s performance in the context of Malaysia - Irma Tyasari; Imran Arshad; Supami Wahyu Setiyowati (BISMA (Bisnis dan Manajemen), 2024)
This research aims to empirically explore the extent to which organisational learning and product innovation explain the relationship between Management Control System (MCS) package, corporate governance, and organisational performance. This research used cluster sampling for data collection. Collected data from 369 managers/owners of small and medium enterprises (SMEs) in Malaysia were used to run partial least square (PLS) regression models and test research hypotheses. The deductive reasoning method is used to develop the theoretical framework. MCS package and corporate governance are positively associated with product innovation and organisational learning. The results reveal that MCS package, corporate governance, organisational learning, and product innovation are positively associated with organisational performance. Organisational learning and product innovation significantly mediate the MCS package, corporate governance, and organisational performance. This research signifies that SMEs managers/owners in Malaysia that MCS package, corporate governance, organisational learning, and product innovation significantly determine organisational performance. In order to boost its performance, they may consider financial and non-financial aspects. The Malaysian government uses the outcomes of this research for the betterment of SMEs in Malaysia.